Placing the Taste of Vermont Cheese - Paxson, Heather (Cuizine)

(untitled) (McGill University Library, 2010)
This essay considers two ways in which farmstead cheesemakers in Vermont are translating the term “terroir” in order to convey the instrumental as well as gustatory values of their artisanal products. In the first, familiar from European systems of geographical indication, terroir calls attention to the material qualities of a locale that may carry through to the taste of a handmade cheese. But in the second, terroir talk offers a more prescriptive reading of the “taste of place” to encourage rural economic revitalization through artisan cheese production. What coalesces in Vermont farmstead cheese as the taste of place reflects, above all, cheesemakers’ entrepreneurial creativity and commitment to making a living by working the land.